Impact of innovation climate on individual and organisational level factors in Asia and Europe - Übius, Ülle; Alas, Ruth; Elenurm, Tiit (Journal of Business Economics and Management, 2013)
Organisation climate plays an important role for the innovation of an organisation. The purpose of this paper is to investigate connections between the innovation climate and individual and organisational level factors. Surveys were conducted among Japanese, Chinese, Estonian, Czech and Slovakian enterprises. Linear regression analysis was conducted. The results of an empirical study show that the innovation climate predicts differently some individual and organisational level factors in studied countries. Two innovation climate facets – commitment and freedom predict individual level factors– attitude toward the firm in all 5 countries. In two studied Asian countries, Japan and China, commitment predicts meaning of work and job satisfaction whereas in all three new European Union member states some links between facets of the innovation climate and individual meaning of work and job satisfaction were missing. Although individual job satisfaction and meaning of work in is still shaped by to some extent different mechanisms in studied countries, implications of the innovative climate for organisation are more similar, at least in industries that are influenced by rapid technological development and globalization.